Existing Model of Used Cooking Oil-Based Biodiesel Management in East Java - Angkoso, Kurniawan Sekar; Marjono, Marjono; Wanto, Alfi Haris; Qurbani, Indah Dwi (Jurnal Pembangunan dan Alam Lestari, 2023)
This research aims to find out the management model of biodiesel based on used cooking oil in East Java. In this study, researchers used a research method with a qualitative approach. The result of this research is that the management of biodiesel based on used cooking oil in East Java technically, no special field handles these problems, so the relationship between related agencies could have gone better. In the research findings in the field, the current model still needs to improve. The use of interpretive qualitative methods was to provide satisfactory information related to the required aspects of the research and for researchers to closely assess the respondents' views on the challenges of recycling used cooking oil to produce biodiesel. The management of used cooking oil-based biodiesel in East Java technically does not have a special field that handles this problem, so relations between related agencies do not run well. In the policy-making process, there has also yet to be an adjustment to the existing characteristics of society, resulting in the policy for managing used cooking oil-based biodiesel not being optimal. Keywords: existing model, biodiesel, management